Polycythemia vera: Perioperative anesthetic challenges and review of literature - Suman Saini; Swati Singhal; Rama Wason (The Indian Anaesthetists' Forum, 2019)
Among the hematopoietic stem cells disorders, polycythemia vera (PV) constitutes a rare entity. The excess production of erythrocytes with thrombocytosis and leukocytosis in patients lead to both thrombotic and hemorrhagic complications. These complications may cause significant perioperative morbidity and mortality. Anesthetic challenges in a patient of PV and brief review of literature are described in this report.